Cirurgia de Bankart artroscópica: Resultados clínicos com seguimento mínimo de 10 anos - Godinho, Pedro Couto; Godinho, André Couto; Rondon, João Victor de Campos Gomes; Oliveira Neto, Francisco Cabral de; Alves, Thiago de Abreu; Godinho, Glaydson Gomes (Revista Brasileira de Ortopedia, 2021)
Objetivo Avaliar o desfecho funcional dos pacientes submetidos ao reparo de Bankart artroscópico no longo prazo.Métodos Avaliação retrospectiva de 41 pacientes (45 ombros) operados entre 1996 e 2009 acompanhados por um período médio de 14,89 anos. Foram feitas análises das pontuações funcionais de University of California, Los Angeles (UCLA) e Carter-Rowe, exame físico e análises de prontuários.Resultados O escore Carter-Rowe apresentou melhora média de 46,11 pontos, com média final de 85,89 pontos, e o UCLA apresentou melhora de 31,33 pontos. Um total de 10 pacientes (22,22%) apresentou recidiva, sendo o número de luxações pré-operatórias o fator mais correlacionado.Conclusão Foi demonstrado que o número de luxações pré-operatórias influenciou negativamente na taxa de falha.Objective To evaluate the functional outcome of patients submitted to arthroscopic Bankart repair in the long-term.Methods Retrospective evaluation of 41 patients (45 shoulders) operated between 1996 and 2009 followed-up for a mean period of 14.89 years. Functional scores were analyzed by the University of California, Los Angeles (UCLA) and Carter-Rowe scores, physical examination, and analysis of medical records.Results The Carter-Rowe score showed an average improvement of 46.11 points, with a final average of 85.89 points, and the UCLA score showed an average improvement of 31.33 points. Ten patients (22.22%) relapsed, with the number of preoperative dislocations being the most correlated factor.Conclusion It was demonstrated that the number of preoperative dislocations negatively influenced the failure rate.
Keywords: ombro; instabilidade articular; artroscopia; recidiva